Knowledge driven service innovation and management IT strategies for business alignment and value creation - Chew, Eng K.; Gottschalk, Petter (Premier reference source, 2013)
"This book provides a comprehensive collection of research and analysis on the principles of service, knowledge and organizational capabilities, clarifying IT strategy procedures and management practices and how they are used to shape a firm's knowledge resources" - Provided by publisher